Short Story Writing Model to Cultivate Creativity and Digitalpreneurship - Dian Nuzulia Armariena; Agus Nuryatin; Teguh Supriyanto; Nas Haryati Setyaningsih; Edward Harrington (Pandawan, 2026)
In the context of higher education, particularly within teacher training institutions, there is a growing need for innovative instructional models that integrate scientific understanding with creative and entrepreneurial competencies. Writing short stories based on scientific principles provides a medium for students to merge analytical thinking with imaginative expression, fostering skills essential for the digital era. This study aims to design and assess a short story writing learning model grounded in scientific principles to foster university students’ creativity and digitalpreneurial thinking. The research was implemented across three higher education institutions in South Sumatra Sriwijaya University (UNSRI), PGRI University of Palembang (UPGRIP), and Tridinanti University of Palembang (UNANTI) using a Research and Development (R&D) methodology that included needs analysis, model design and validation, and effectiveness testing. The model was validated by experts, refined based on academic and practitioner feedback, and its effectiveness was evaluated through statistical analysis, including normality and homogeneity testing followed by a paired sample t-test. The findings demonstrated a significant improvement in students’ short story writing performance, confirming the model’s effectiveness in enhancing both creative and analytical writing abilities while supporting contextual and interdisciplinary learning. The study concludes that the scientific-based short story writing model not only strengthens students’ academic and creative competencies but also nurtures entrepreneurial mindsets relevant to the digital era.